PARADIGMA FILSAFAT BAHASA DALAM PERKEMBANGAN SASTRA INDONESIA - Permata, Nindya; Yuliatin; Pangestu, Abi; Amalia Kurnia Sari, Riska; Himawan, Riswanda (Buana Bastra, 2026)
This study aims to analyze the role of the philosophy of language in the development of Indonesian literature and its influence across different literary periods. The research employs a qualitative method with a descriptive-analytical approach, focusing on theories of the philosophy of language and their relationship to Indonesian literary works from various periods. The findings indicate a shift in paradigms within the philosophy of language, encompassing structuralism, poststructuralism, and hermeneutics. These paradigm shifts have contributed to the emergence of diverse variations in literary forms, themes, and aesthetic strategies in Indonesian literature.